2010
DOI: 10.1111/j.1528-1167.2009.02401.x
|View full text |Cite
|
Sign up to set email alerts
|

Meta‐analysis of the association between cysticercosis and epilepsy in Africa

Abstract: Summary Purpose:  The association between cysticercosis and epilepsy has been widely studied in Latin America and Asia and has proven to be one of the main causes of epilepsy. Despite high prevalences of both diseases in Africa, their association remains unclear. In this article we quantified the strength of the association between epilepsy and cysticercosis in Africa and we proposed some guidelines for future studies. Methods:  We performed a systematic review of literature on cysticercosis (considered as exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
56
1
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(64 citation statements)
references
References 37 publications
4
56
1
2
Order By: Relevance
“…In those areas already subject to ivermectin mass therapy, the prevalence of palpable nodules and nodule load may be used as indicators for intensity of infection at least during the first years after the start of control campaigns when only minor changes of nodule counts are expected. 32 More rigorous casecontrolled studies using the example of those studies carried out on cysticercosis 33 are needed to enhance our understanding of the enigmatic phenomenon of river epilepsy. …”
Section: Discussionmentioning
confidence: 99%
“…In those areas already subject to ivermectin mass therapy, the prevalence of palpable nodules and nodule load may be used as indicators for intensity of infection at least during the first years after the start of control campaigns when only minor changes of nodule counts are expected. 32 More rigorous casecontrolled studies using the example of those studies carried out on cysticercosis 33 are needed to enhance our understanding of the enigmatic phenomenon of river epilepsy. …”
Section: Discussionmentioning
confidence: 99%
“…Epidemiological studies from sub-Saharan Africa have shown the association of neurocysticercosis with seizures or epilepsy (Gemmell & Johnstone, 1976;Andriantsimahavandy et al, 1997;Pal et al, 2000;Carpio, 2002;Nsengiyumwa et al, 2003;Wagner & Newton, 2009;Coyle et al, 2012;Millogo et al, 2012). Evidence from neuroimaging studies in people with epilepsy and the recent meta-analysis and systematic review which included only studies conducted in sub-Saharan Africa demonstrated a significant association between neurocysticercosis and epilepsy, suggesting that neurocysticercosis could be the major contributing factor for the high prevalence of epilepsy observed (Carpio et al, 1998;Nsengiyumwa et al, 2003;Quet et al, 2010;Ndimubanzi et al, 2010). The major limitation on establishing evidence on the association of neurocysticercosis and epilepsy in sub-Saharan Africa is the lack of longitudinal surveys to examine the incidence of epilepsy following infections with T. solium (Blocher et al, 2011) or the impact of T. solium treatment using praziquantel on the prevalence of epilepsy.…”
Section: Tropical Parasitic Infections Associated With Epilepsy In Sumentioning
confidence: 99%
“…It is estimated that people with cysticercosis have a 3.4 to 3.8-fold increased risk for developing epilepsy [4].…”
Section: Introductionmentioning
confidence: 99%